Rhomboids of Mycobacteria: characterization using an aarA mutant of Providencia stuartii and gene deletion in Mycobacterium smegmatis. - David Patrick Kateete; Fred Ashaba Katabazi; Alfred Okeng; Moses Okee; Conrad Musinguzi; Benon Byamugisha Asiimwe; Samuel Kyobe; Jeniffer Asiimwe; W Henry Boom; Moses Lutaakome Joloba (PLoS ONE)
Background Rhomboids are ubiquitous proteins with unknown roles in mycobacteria. However, bioinformatics suggested putative roles in DNA replication pathways and metabolite transport. Here, mycobacterial rhomboid-encoding genes were characterized; first, using the Providencia stuartii null-rhomboid mutant and then deleted from Mycobacterium smegmatis for additional insight in mycobacteria. Methodology/principal findings Using in silico analysis we identified in M. tuberculosis genome the genes encoding two putative rhomboid proteins; Rv0110 (referred to as "rhomboid protease 1") and Rv1337 ("rhomboid protease 2"). Genes encoding orthologs of these proteins are widely represented in all mycobacterial species. When transformed into P. stuartii null-rhomboid mutant (ΔaarA), genes encoding mycobacterial orthologs of "rhomboid protease 2" fully restored AarA activity (AarA is the rhomboid protein of P. stuartii). However, most genes encoding mycobacterial "rhomboid protease 1" orthologs did not. Furthermore, upon gene deletion in M. smegmatis, the ΔMSMEG_4904 single mutant (which lost the gene encoding MSMEG_4904, orthologous to Rv1337, "rhomboid protease 2") formed the least biofilms and was also more susceptible to ciprofloxacin and novobiocin, antimicrobials that inhibit DNA gyrase. However, the ΔMSMEG_5036 single mutant (which lost the gene encoding MSMEG_5036, orthologous to Rv0110, "rhomboid protease 1") was not as susceptible. Surprisingly, the double rhomboid mutant ΔMSMEG_4904-ΔMSMEG_5036 (which lost genes encoding both homologs) was also not as susceptible suggesting compensatory effects following deletion of both rhomboid-encoding genes. Indeed, transforming the double mutant with a plasmid encoding MSMEG_5036 produced phenotypes of the ΔMSMEG_4904 single mutant (i.e. susceptibility to ciprofloxacin and novobiocin). Conclusions/significance Mycobacterial rhomboid-encoding genes exhibit differences in complementing aarA whereby it's only genes encoding "rhomboid protease 2" orthologs that fully restore AarA activity. Additionally, gene deletion data suggests inhibition of DNA gyrase by MSMEG_4904; however, the ameliorated effect in the double mutant suggests occurrence of compensatory mechanisms following deletion of genes encoding both rhomboids.